Be Wise on the Internet in the Digital Era - Feri Alpiyasin; Rini Risanti; Yomanius Untung; Dylan Hafizh Ramdany; M Fahmi Aditia; M Adika Burhanuddin; Rafi Iqbal Maulana; Wahyuni Syifa Aliyya; Nasywa Ambarwati; Najhan Taswiyah Hasanudin; Ibnu Raihan Raindra A; Bagaskara Saputra D; Manan Prasetya; Andika Maulana Yusuf (LPPM STMIK Mardira Indonesia, 2025)
Prudent internet use in the digital age seeks to mitigate the imprudent actions of adolescent internet users. The primary concerns identified encompass insufficient understanding of mental health dangers, the proliferation of misinformation, and internet addiction. This community service initiative utilizes a socialization approach comprising steps such as a pre-test, a material presentation, a post-test, and an implementation evaluation. Findings from this community service initiative reveal that people in Karanganyar and Astanaanyar who participated in the digital literacy workshop demonstrated enhanced comprehension of safe and responsible internet use. In conclusion, digital literacy education equips the community with essential skills to navigate the online realm responsibly, thereby reducing risks and enhancing the benefits of the internet in the digital age.